Molecular basis of type III hyperlipoproteinemia in Germany - Feussner, Giso; Feussner, Vera; Hoffmann, Michael M.; Lohrmann, Jens Dieter Wolfgang; Wieland, Heinrich; März, Winfried (Human mutation, 1998)
Type III hyperlipoproteinemia (HLP) is usually associated with homozygosity for apolipoprotein (apo) E2 (Arg112→ Cys, Arg158→ Cys). This common apo E isoform is defective in its binding to lipoprotein receptors. However, other rare mutations in the apo ϵ gene may also, in part dominantly, predispose to the disease. In order to assess the prevalence of rare apo E variants and mutations in the apo ϵ gene in Germany, we examined apo ϵ genotypes by restriction isotyping (RI) and apo E phenotypes by isoelectric focusing (IEF) in 107 German patients with type III HLP. Concordance between apo ϵ genotype and apo E phenotype was observed in 101 subjects (94.4%). Six individuals (5.6%) had genotypes and phenotypes other than E2/2. One subject was apparently homozygous for apo E2 by IEF, but heterozygous for ϵ3/2 by RI. Sequencing of the apo ϵ gene disclosed a hitherto undescribed point mutation (TGG→ TGA) at the third position of the codon for amino acid 20 (Trp), introducing a premature termination codon. This is the first study demonstrating that in the German population type III HLP is mainly associated with homozygosity for apo E2 (Arg112→ Cys, Arg158 → Cys) and that discrepancies between apo ϵ genotype and apo E phenotype are rare in this genetic condition. Hum Mutat 11:417-423, 1998. © 1998 Wiley-Liss, Inc.
Elektronische Reproduktion der Druck-Ausgabe 22. November 1999
Gesehen am 30.01.2025